STRATEGI PEDAGANG KAKI LIMA UNTUK MENINGKATKAN PENDAPATAN DI KAWASAN PASAR LUBUK BUAYA KECAMATAN KOTO TANGAH KOTA PADANG - M.Putra Aidil Adha; Deded Chandra (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
ABSTRACT M. Putra Aidil Adha. FIVE FOOT TRADERS 'STRATEGIES TO INCREASE REVENUE IN THE LUBUK BUAYA PASAR AREA, KECAMATAN KOTO TANGAH, KOTA PADANG. Thesis, Padang: Faculty of Social Sciences. Padang State University 2021. This study aims to find information and find out about (1) the strategy of street vendors in increasing income in the Lubuk Buaya Market area, Koto Tangah District, Padang City. (2) Constraints faced by street vendors in increasing income. (3) Distribution of street vendors in the Lubuk Buaya Market Area, Koto Tangah District, Padang City. The type of research used in this research is the Mix Method, namely qualitative and quantitative. In this study the qualitative approach is used to determine the distribution of street vendors in the Lubuk Crocodile market area, strategies to increase income, and the obstacles faced in increasing income while quantitative. used to determine the percentage of street vendor income by using a percentage descriptive formula. Data collection techniques in this study are by means of interviews, questionnaires or questionnaires, and documentation. Then for data analysis techniques using data reduction, data presentation, data verification and followed by a description of the percentage. The result of this research is that it can be seen that (1) The distribution of street vendors in the Lubuk Buaya Market area forms an elongated pattern along the road around the market area. (2) The strategies used by street vendors in the Lubuk Buaya Market Area are maintaining product quality, especially for food traders, namely by maintaining the quality of the taste of the food being traded, increasing business capital, and paying attention to business locations by paying attention to locations and places of sale such as paying attention to cleanliness, and selling in a crowded location is a strategy to increase the income of street vendors as well. (3) obstacles faced by street vendors in the Lubuk Buaya Market Area in increasing income, namely bad weather, insufficient business capital, inadequate place of business.